The first host plant dataset of Curculionidae Scolytinae of the world: Hylastini LeConte, Hylurgini Gistel, Ipini Bedel, Phloeosinini Nusslin, Polygraphini Chapuis - Matteo Marchioro; Michele Rossini; Giacomo Ortis; Enrico Ruzzier; Davide Vallotto; Laura Besana; Massimo Faccoli (Scientific Data)
Abstract Wood-boring beetles and, in particular, Scolytinae (Coleoptera: Curculionidae) are one of the most successful groups of invasive species worldwide. They can be easily transported across continents at the larval stage as their development takes place inside the tissues of live plants, timber, wood products and wood-packaging materials. This grants them protection from adverse travel conditions and allows them to often go unnoticed by phytosanitary inspections at ports of entry. In this context, knowledge of biological traits of these species, particularly the recorded host plants, is essential for planning effective monitoring strategies. This kind of information is scattered through a large amount of papers, catalogs and books. Thus, the purpose of this paper is to provide a comprehensive list of host plants and their economic categorization for five scolytine tribes. This fourth contribution presents the list of host plants for 829 species belonging to five tribes that mainly, but not exclusively, infest conifers: Hylastini LeConte, Hylurgini Gistel, Ipini Bedel, Phloeosinini Nusslin, and Polygraphini Chapuis.